The drunken botanist [compact disc, unabridged] : the plants that create the world's great drinks - Stewart, Amy (HighBridge Audio, 2013)
Every great drink starts with a plant. Sake began with a grain of rice. Scotch emerged from barley. Gin was born from a conifer shrub when a Dutch physician added oil of juniper to a clear spirit, believing that juniper berries would cure kidney disorders. This uncovers the enlightening botanical history and the science and chemistry of over 150 plants, flowers, trees, and fruits (and even one fungus).